Coaching Mampu Meningkatkan Motivasi, Kreativitas, dan Kinerja Guru Kelas IV Mupel IPAS di Gugus Diponegoro - Siti Khomsatun; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2023)
The motivation, creativity, and performance of teachers in fulfilling their duties and responsibilities play a crucial role in enhancing the learning process and improving the quality of education. For this reason, the role and support of the school principal is very important in fostering teacher motivation, creativity and performance, especially in learning of Social Sciences (IPAS) lessons in the classroom. This study attempts to apply coaching techniques with the aim of: (1) increasing teacher motivation through coaching: (2) increasing teacher creativity in Social Sciences (IPAS) lessons through coaching; (3) improving teacher performance in learning of Social Sciences (IPAS) lessons for 4th grade at the Diponegoro Cluster for the 2022/2023 academic year. The design of this research is School Action Research (SAR). The cycle in this SAR is one pre-cycle and two action cycles with four stages which include planning, implementing actions, observing, and reflecting. The data from this study were sourced from class IV teachers who were in the Diponegoro Purworejo cluster, totaling 9 teachers. Data collection techniques using questionnaires, observations, and test results. Furthermore, the data were analyzed in a quantitative descriptive manner using the percentage technique. The results of this study are: (1) there is an increase in teacher motivation from pre-cycle (33.3%), cycle I (66.67%), and cycle II (88.89%); (2) there was an increase in the number of teachers who had high creativity from pre-cycle (59.4%), cycle I (66.11%), and cycle II (84.4%); (3) there was an increase in teacher performance at the Pre-cycle stage, increasing from (44.4%) to (77.78%) in Cycle I and to (88.89)% in Cycle II. Thus, the application of coaching to teachers is proven to be able to increase teacher motivation, creativity, and performance in science content for class IV teachers in the Diponegoro Purworejo Cluster for the 2022/2023 academic year.